To assess the impact of physical factors on velocity, speed, and accuracy of tennis serve - Ma, Xudong; Yaacob, Azhar; Tengku Kamalden, Tengku Fadilah; Ng, Yee Guan (Think Biotech Limited, 2024)
Real-world variables significantly influence the velocity of a tennis serve. Key factors include biomechanical components, anthropometrics, and strength and conditioning practices. Objective: This study investigates the coordination of racquet and ball speed, examining how physical attributes and training impact serve performance. Methods: An exhaustive review was conducted using Google Scholar, analyzing 25 key papers related to tennis serve velocity, biomechanics, and training programs. The focus was on identifying the contributions of lower and upper body strength, as well as trunk stability, to serve velocity. Results: The analysis revealed that Increased lean muscle mass, arm length, and body height correlate with faster serves. Maximizing isometric strength and optimizing force production at joint Am J Sports Medic chains enhance serve velocity. Only a minor portion of the force exerted on the ball (less than 50%) is generated by the trunk and lower body, yet they significantly influence the velocity. Variations in serve velocity improvements ranged from 3.0% to 29.0% across studies, with disparities potentially due to different study durations (four weeks to nine months) and methodologies. Match fatigue significantly reduces serve velocity and stroke volume (SV) over time. Shoulder injuries are primarily caused by imbalances between agonist and antagonist muscles, despite advancements in serve velocity. Conclusion: Efficient and effective training models are essential for improving tennis serve performance. Enhancements in isometric strength, force production, and muscle mass are crucial, alongside careful monitoring and recovery to manage the physical demands on athletes. Incorporating resistance training that focuses on both lower and upper body strength, as well as trunk stability, into a periodized strength and conditioning program, is recommended to optimize serve velocity and overall athletic performance.